Bentuk Kesalahan Penerjemahan Bahasa Jepang-Bahasa Indonesia - Adi Nugroho (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2022)
This study intends to identify the types of errors produced by Honyaku 1 course students in the Study Program of Japanese Language Education, Faculty of Language and Arts (FBS) State University of Jakarta (UNJ) in the 2020/2021 academic year while translating sentences from Japanese to Indonesian. The source of this research data is the result of student translations. This study employs a descriptive approach, in which the outcomes of sentence translations are analyzed to identify types of faults in the translation of Japanese to Indonesian by analyzing the types of translation errors identified in the target language (TL) and determining the equivalence of meaning between source language sentences (LS) and target language sentences. This research takes a descriptive qualitative method. According to the findings of the study, the most common types of translation errors are interference problems, both in terms of lexical and grammatical characteristics. Meanwhile, based on the severity of the problem,students' translation faults are classified as global errors, which comprise both lexical and grammatical errors.